Norwegian Interbank Market's Response to Changes in Liquidity Policy - Q. Farooq Akram; Jon H. Findreng (Norges Bank, 2017)
We investigate pricing and activity in the Norwegian unsecured overnight interbank market in response to a shift in the central bank's liquidity policy. In October 2011, to encourage interbank trading, banks were allotted quotas for their overnight deposits with remuneration at the key policy rate while that on overnight deposits beyond allotted quotas was set one percentage point lower. In addition, a target range for banks' total overnight deposits was introduced and supported by open market operations to counteract not only temporary liquidity shortfalls, but also surpluses. We document substantially higher interbank trading, lower interbank interest rates relative to the policy rate as well as lower interest rate volatility following the policy shift. Notably, while overnight interbank interest rates were generally above the key policy rate before the policy shift, they have been close to but generally below the key policy rate afterwards.
hdl:11250/2495584
Keywords: G21; E43; E58; 330; overnight interbank market; liquidity policy; regime-switching models